On the Complex Formation of Antithrombin III with Thrombin - Binder, B (Thrombosis and Haemostasis, 1973)
Based on gelfiltration studies, the part of AT III which becomes bound to thrombin during the process of in vitro blood coagulation was calculated to be about 40% of total AT III. Complexes consisting of one AT III and one thrombin molecule could not be detected while fractions corresponding to molecular weights of about 190,000 Dalton show AT III as well as thrombin activities. The AT III - thrombin complex in normal human serum consists, therefore, of either 2 AT III and 2 thrombin molecules or of one AT III and 4 thrombin molecules.